Muros de domínio e ricochetes na gravitação massiva tridimensional - Louzada, Hugo Leonardo Costa (2010)
Flat domain walls solutions of three dimensional new massive gravity extended by massive scalar with Higgs-like self-interaction are constructed by Superpotential method. The properties of the cosmological bounce-like solution are investigated. Depending on the values of the cosmological constant ? and of the graviton mass m2 they describe qualitatively different evolutions of the 3D universe including the one of two periods of acceleration between two dS3 representig initial/final states.